Research on the Compound Crank-link Mechanism with Precise Sine Output Characteristics - Xiao Yong; Zhang Rui; Zou Zhengyao; Lu Junfeng (Jixie chuandong)
Aiming at the transmission characteristics of the second harmonic of a single crank connecting rod mechanism, a composite crank connecting rod mechanism with output precise sinusoidal velocity-time characteristics is innovatively proposed. The output characteristics of the new mechanism are demonstrated through analytical analysis, and its velocity formulas are deduced. Considering the error existing in adjusting the lengths of the two cranks, the influence of the length difference on the output error is analyzed. The Adams software is used to simulate the mechanism. When the difference between the lengths of the two cranks is 0.5 mm, the error between the speed output law and the standard sine curve is small. The research results show that the mechanism reduces the velocity-time errors of a single crank-link mechanism from 25% to less than 1%, which can meet the requirements of low cost in the initial test of products such as tidal energy power generation devices and automobile suspension vibrations. It also meets the requirements for rapid experimentation.